(untitled) (Nigerian Journal of Technology, 2018)
At speeds greater than 100km/h, the performance, handling, safety, and comfort of a car are significantly affected by its aerodynamic properties. In a bid to improve on the aerodynamics of cars, rear spoilers/wings are increasingly being used both on race and passenger cars. This paper employs Computational Fluid Dynamics (CFD) techniques to investigate the aerodynamic effects of rear spoilers on Drag and Lift of a car. In carrying out this study, a rear spoiler already designed was used. The spoiler was modelled in CAD software (Autodesk Inventor professional) along with a model car that it will be mounted upon. Two cases were set; the car alone without the rear spoiler (case 1) and, the car with the rear spoiler assembled on its rear deck (case 2). These two cases were imported into CFD software (ANSYS Fluent 15.0) for simulation. The Drag and Lift on the two cases were obtained in terms of their coefficients from the analysis. From the results obtained, it was observed that using a wing type rear spoiler led to an increase in downward force (negative lift), and a consequent increase in drag on the car. The increased downward force on the car will reflect in an increased cornering ability and stability of the car at high speed, while the attendant Drag entails increased fuel consumption. From the amount of downward force generated compared to Drag, and given that safety is put first above going faster; the benefits of using the rear spoiler outweighs that of not using it. http://dx.doi.org/10.4314/njt.v37i4.17